2022
DOI: 10.1177/01945998221114078
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sinonasal Computed Tomography Scores to Patient‐Reported Outcome Measures: A Systematic Review and Meta‐analysis

Abstract: Objective To perform a systematic review of proposed sinus computed tomography (CT) scoring systems and determine their association with patient-reported outcome measures (PROMs). Data Sources PubMed, CINAHL, Scopus, and Cochrane Library. Review Methods A systematic search was conducted following the PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta-analyses) for studies describing CT scores and PROMs in patients with chronic rhinosinusitis. Results A total of 144 studies were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 46 publications
2
11
1
Order By: Relevance
“…Perhaps this difference in severity objective findings on imaging plays a role in delaying surgical treatment for females or in raising the threshold above which females are offered surgery, particularly in patients with headache or facial pressure as a main symptom. Importantly, multiple studies have consistently failed to correlate symptom severity on PROMs with CT grade, 63,64 although Zhou et al 65 did find an association between the SNOT-22 nasal subdomain and Lund Mackay score (but not with overall SNOT-22). Given the lack of correlation between CT and PROM disease burden, it is not altogether surprising that males exhibit more severe disease on imaging, whereas females report more severe symptoms on PROMs.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps this difference in severity objective findings on imaging plays a role in delaying surgical treatment for females or in raising the threshold above which females are offered surgery, particularly in patients with headache or facial pressure as a main symptom. Importantly, multiple studies have consistently failed to correlate symptom severity on PROMs with CT grade, 63,64 although Zhou et al 65 did find an association between the SNOT-22 nasal subdomain and Lund Mackay score (but not with overall SNOT-22). Given the lack of correlation between CT and PROM disease burden, it is not altogether surprising that males exhibit more severe disease on imaging, whereas females report more severe symptoms on PROMs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the severity of radiographic opacification of the paranasal sinuses has been shown to be poorly correlated with patient-reported outcome measures (PROMs) or quality of life (QOL), highlighting its lack of utility as a reflection of the patient's experience. 26 Sinus-specific opacification has also been shown to not be correlated with CRS symptomatology. 27 Although the evidence has been conflicting, 28,29 some studies have shown that greater radiographic CRS disease severity may be associated with better outcomes after ESS [30][31][32] and one retrospective study has suggested that symptoms/ revision ESS rate may not be improved by ESS beyond affected sinuses.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the severity of radiographic opacification of the paranasal sinuses has been shown to be poorly correlated with patient‐reported outcome measures (PROMs) or quality of life (QOL), highlighting its lack of utility as a reflection of the patient's experience 26 . Sinus‐specific opacification has also been shown to not be correlated with CRS symptomatology 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Newer technology, however, has allowed for volumetric scoring of sinus opacification which provides an additional evaluative element – and again, with volumetric assessment, olfactory cleft opacification has correlated with olfaction testing [36]. Although the modified Lung–Mackay score has been found to be a predictor of the recurrence of polyps in patients with CRS [37 ▪▪ ], it is unclear whether imaging findings correlate well with patient-perceived symptomatology, given only a very weak correlation between Lund–Mackay score and SNOT-22 scores is a recent large meta-analysis [38].…”
Section: Clinically Assessed Outcome Measuresmentioning
confidence: 99%